2016
DOI: 10.1128/jvi.02790-15
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Stabilizing Mutations in an H5 Hemagglutinin Influenza Virus Protein

Abstract: Highly pathogenic avian influenza viruses of the H5N1 subtype continue to circulate in poultry in Asia, Africa, and the Middle East. Recently, outbreaks of novel reassortant H5 viruses have also occurred in North America. Although the number of human infections with highly pathogenic H5N1 influenza viruses continues to rise, these viruses remain unable to efficiently transmit between humans. However, we and others have identified H5 viruses capable of respiratory droplet transmission in ferrets. Two experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…Previously, we found that an L415I (418 in H3 numbering) change in seasonal H1N1 strains accounted for the resistance of H1 HA pseudoviruses to cross-neutralizing human sera ( 35 ). The same mutation was also reported to increase the stability of H5 HA ( 36 ), though 419I is not naturally present in the H5 sequences that we studied.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Previously, we found that an L415I (418 in H3 numbering) change in seasonal H1N1 strains accounted for the resistance of H1 HA pseudoviruses to cross-neutralizing human sera ( 35 ). The same mutation was also reported to increase the stability of H5 HA ( 36 ), though 419I is not naturally present in the H5 sequences that we studied.…”
Section: Resultssupporting
confidence: 69%
“…Levels of HA stability differ among different strains. D94N (101 in H3 HA numbering), S217P (221 in H3 HA numbering), M226V (230 in H3 HA numbering), and L419I (418 in H3 HA numbering) have been reported to increase H5 HA stability ( 36 ). Among the H5 HAs that we investigated here, we noted that (i) the HAs of AH/1, TK/1, and OS/102 contain 94N, (ii) the HA of ID/5 contains 94S, (iii) the HA of GX/13 contains 94I, (iv) the HA of HK/156 contains 94N and 217P, and (v) the HA of HK/3088 contains 94N and 217I.…”
Section: Discussionmentioning
confidence: 99%
“…Such research could use all of the approaches described above and higher-throughput assays that could be developed with improved technology, for example as described in Box 3. This will include generating mutations not found in known strains in nature to probe for those that could be involved in human adaptation in the future (Hanson et al, 2015; Thyagarajan and Bloom, 2014). The goal would be to identify classes of functionally equivalent substitutions, sufficient individually or in defined combinations to confer a trait of interest when introduced into a defined, avian-adapted genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…2g ). It has been well proved that Q226I/L in the RBP increased the ability to bind a2–6 sialic acid 26 30 , which implies its role in inter-molecular interactions is more important than that in intra-molecular interactions in HA. Besides, dual mutations E190D and G225D of receptor binding sites had no effect on H-bonds in H1 HA according to our assessment (Fig.…”
Section: Discussionmentioning
confidence: 99%